Model intensitas hujan akibat pemanasan global pada DAS Cidanau Kabupaten Serang Provinsi Banten - Anas, Mochamad Azwar; Aswad, Hanafi; Sar, Mas ud (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
More frequent extreme rainfall can cause floods and landslides in some areas of Banten, especially in mountainous and hilly areas, The increase in air temperature in Banten tends to increase in recent decades. This can affect agricultural productivity and increase the risk of forest and land fires. Uncertain rainfall patterns can affect the agricultural sector and the availability of clean water in Banten, to overcome the impact of climate change, the Banten Provincial Government has taken several mitigation and adaptation measures, such as improving flood control infrastructure, planting mangroves in coastal areas, and implementing agricultural practices that are more resilient to climate change. The purpose of this study is to determine the model of the intensity and influence of climate variables on the intensity of rainfall due to global warming in the Cidanau watershed, Serang Regency, Banten Province. The methods used in this study are frequency analysis, probability, compatibility test and rain intensity analysis based on climate simulation. The results of this study obtained a model of the intensity of climate parameters that have the most influence on the intensity of rain for the simulation of 1 variable is air humidity (Rh) with the equation I (RH) = 166,10 X-0,666 , For the simulation, 2 variables are wind speed and air humidity (W-RH) with the equation I (W-RH) = 177,84 X-0,666 and the highest influence is the simulation of 3 variables of temperature, wind speed, and air humidity (T-W-RH) simultaneously with the equation I (T-W-RH) = 190,70 X-0,666.